The product of two consecutive odd integers is 899.
Let x be the first odd integer.
Then (x+2) will be the second odd integer.
Their product must be equal to 899, so we can write
![x\cdot(x+2)=899](https://img.qammunity.org/2023/formulas/mathematics/college/b2hg89of8d24vqbd8leib2e6pagt9imcdd.png)
Simplify the equation
![\begin{gathered} x^2+2x=899 \\ x^2+2x-899=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/58l9ccjs6ymafr8wx6eqnexmnd6iulrg8v.png)
This is a quadratic equation that can be solved by either factoring or using the quadratic formula.
Let's use the quadratic formula.
![x=(-b\pm√(b^2-4ac))/(2a)](https://img.qammunity.org/2023/formulas/mathematics/college/jr19ixi2zltkocy82qhxfiop5lyv4hzbkm.png)
For the given case, the coefficients are
a = 1
b = 2
c = -899
![\begin{gathered} x=\frac{-2\pm\sqrt[]{2^2-4(1)(-899)}}{2(1)} \\ x=\frac{-2\pm\sqrt[]{3600}}{2} \\ x=(-2\pm60)/(2) \\ x=(-2+60)/(2),\; x=(-2-60)/(2) \\ x=(58)/(2),\; x=(-62)/(2) \\ x=29,\; x=-31 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/iq0rdzeiiyhtbl6thfbw5xdlb8gw3n9s45.png)
So, the first integer is 29
The second odd integer is x + 2 = 29 + 2 = 31
Verify the results
![29*31=899](https://img.qammunity.org/2023/formulas/mathematics/college/av7ejar2q9yb9vcgpm4b7qnpxs99qvl2nz.png)
Also, -31 is the first integer.
The second integer is x + 2 = -31 + 2 = -29
Verify the results
![-31*-29=899](https://img.qammunity.org/2023/formulas/mathematics/college/rwpc6ghiur1dmf9s0mx2u91ghrm5hj16sk.png)
Therefore, the solution is
![\mleft\lbrace29,31\mright\rbrace\; and\; \mleft\lbrace-31,-29\mright\rbrace](https://img.qammunity.org/2023/formulas/mathematics/college/mdh8u3e6p1gjejpg2p4nd8iohhyf74e22i.png)